Efektivitas Penggunaan Teknologi Informasi dalam Pembelajaran Daring pada Masa Covid-19 - Zulhendri, Zulhendri; Yunita, Rika Gusri; Hayeni, Fitri (UIN Imam Bonjol Padang, 2021)
This study aims to find out how to describe the effectiveness of the use of information technology in online learning during the Covid-19 period at SDN 04 Koto Tuo Sulit Air. This research is descriptive quantitative research. The population in this study were all students of SDN 04 Kototuo Sulit Air in the 2020/2021 school year. The data was collected by distributing questionnaires online to 57 students who became respondents consisting of 18 grade IV students, 19 class V students and 20 grade VI students. The results illustrate that 1) As many as 89.47% of students stated that the use of information technology was effective in online learning, while 10.52% of students stated that the use of information technology was not effective in online learning, 2) Students stated that the most effective platform in learning online is WhatsApp at 50.88%, 3) Students state that the least effective platform in online learning is the zoom meeting of 47.37%